The History of Archaeology as a ‘Colonial Discourse’ - Oscar Moro-Abadía (Bulletin of the History of Archaeology, 2006)
During the greater part of the twentieth century, the history of archaeology promoted an idealized image of archaeological practice in colonized places. Historians usually omitted the political implications of archaeology and, in many instances, justified the appropriation of material culture from colonized places. In this paper, I suggest that postcolonial studies, a field constituted during the 1980s and 1990s, offers a useful framework in which to understand the relationships between the history of archaeology and colonialism. Taking postcolonial theory as reference, I define the history of archaeology written until the 1980s as a particular form of ‘colonial discourse’. I conclude by proposing some ways in which postcolonial theory can inform the history of archaeology.